Perbaikan proses produksi dan ijin edar guna meningkatkan mutu produk unggulan daerah - Suprayogi, Suprayogi; Sabrina Sunyoto, Nimas Mayang; Syamsul Hadi, Mochammad; Fadhilah, Umi; El Afwa, Muthia; Nur Aziza, Nadya Lulu; Zulismar, Reni; Nareswari, Bernardia Filia; Firdausyi, Izzati Ardhan (University of Islam Malang, 2021)
KWT